2023
DOI: 10.1140/epjc/s10052-022-11130-1
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence and Landauer’s principle in qubit-cavity quantum-field-theory interaction

Abstract: We consider quantum decoherence and Landauer’s principle in qubit-cavity quantum field theory (QFT) interaction, treating the qubit as the system and cavity QFT as the environment. In particular, we investigate the changes that occur in the system with a pure initial state and environment during the decoherence process, with or without energy dissipation, and compare the results with the case in which the initial state of the system is a mixed state and thus decoherence is absent. When we choose an interaction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…They directly relate the nature of the detector and the quantum field theory, which may provide JHEP03(2023)179 clues for future experiments, especially in the future spacebased experiments Recently it was found that the decoherence rate can be used to measure the Unruh effect [39]. We can also study the exchange of energy and information during the interaction between the detector and quantum field theory [40][41][42], which may help us to understand the feedback and back-reaction obtained from the measurements, as well as the connection between gravity and quantum theory. In [41] we also investigated the decoherence of the qubit coupled to a thermal quantum field theory in a cavity, and the results are also consistent with our Theorem 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They directly relate the nature of the detector and the quantum field theory, which may provide JHEP03(2023)179 clues for future experiments, especially in the future spacebased experiments Recently it was found that the decoherence rate can be used to measure the Unruh effect [39]. We can also study the exchange of energy and information during the interaction between the detector and quantum field theory [40][41][42], which may help us to understand the feedback and back-reaction obtained from the measurements, as well as the connection between gravity and quantum theory. In [41] we also investigated the decoherence of the qubit coupled to a thermal quantum field theory in a cavity, and the results are also consistent with our Theorem 1.…”
Section: Discussionmentioning
confidence: 99%
“…We can also study the exchange of energy and information during the interaction between the detector and quantum field theory [40][41][42], which may help us to understand the feedback and back-reaction obtained from the measurements, as well as the connection between gravity and quantum theory. In [41] we also investigated the decoherence of the qubit coupled to a thermal quantum field theory in a cavity, and the results are also consistent with our Theorem 1. Of course, when we consider the thermal state instead of the Unruh effect, the Fermi-Dirac distribution does not appear in odd dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it was found that the decoherence rate can be used to measure the Unruh effect [38]. We can also study the exchange of energy and information during the interaction between the detector and quantum field theory [39][40][41], which may help us to understand the feedback and back-reaction obtained from the measurements, as well as the connection between gravity and quantum theory. In [40] we also investigated the decoherence of the qubit coupled to a thermal quantum field theory in a cavity, and the results are also consistent with our Theorem 1.…”
Section: From D To D +mentioning
confidence: 99%
“…We can also study the exchange of energy and information during the interaction between the detector and quantum field theory [39][40][41], which may help us to understand the feedback and back-reaction obtained from the measurements, as well as the connection between gravity and quantum theory. In [40] we also investigated the decoherence of the qubit coupled to a thermal quantum field theory in a cavity, and the results are also consistent with our Theorem 1. Of course, when we consider the thermal state instead of the Unruh effect, the Fermi-Dirac distribution does not appear in odd dimensions.…”
Section: From D To D +mentioning
confidence: 99%